STUDY OF VISUAL NARRATIVE STRUCTURE AND IMMERSION ON NARRATIVE VIDEO MAPPING CASE STUDY: NRMO LZY VISUAL IN JOGJAKARTA VIDEO MAPPING FESTIVAL 2018 - Pahrulroji, Andri
The development of media and technology has given birth to a video mapping technique, which known as video mapping or projection mapping, video mapping is currently a unique and attractive visual presentation with a dynamic video display that produces optical illusions, thus began many developed and researched in the field of creative industries and education. Video mapping is known as one of the media that can convey various messages to audiences like any other media, but interestingly, the content on video mapping is closely related and adapts to its facade, making the visual narrative structure contained in the video mapping undoubtedly different. The term "immersion" is often discovered in several virtual reality studies and interactive media, but it has not been found whether immersion can be created in a video mapping show, especially in narrative mapping videos. Video mapping case study NRMO Lzy Visual in Jogjakarta Video Mapping Festival 2018 is one of the shows shown at the first video mapping festival in Indonesia involving several well-known creators in Indonesia. The creators at the festival considered NRMO to be one of the best video mappers that included narration. Therefore, this study aims to determine the structure of the narrative, how the message is delivered, and whether the narrative structure and message can create immersion, primarily narrative immersion, because it will be handy to be a reference for creators or further video mapping research on how the narrative structure, message delivery, and immersion in video mapping are related to one another. The research was conducted through a qualitative descriptive method and pre-experimental design. The researcher will first analyze the facade characteristics and narrative structure of the NRMO mapping video by extracting theory from other knowledge to facilitate the research. Then, recreate the show to show back to the audience as reminders. Interviews were conducted with the audience and analyzed the message conveyed and its immersion based on the taxonomic theory of Nillson, Nordahl and Seraafin, which can distinguish the appreciator immersion condition due to the impact of technology (immersion system), subjective responses to a narrative (narrative immersion), or because of subjective responses to challenges in a virtual environment (challenge-based immersion). The study results found that NRMO video mapping is a narrative video mapping with an art deco-style facade that has the characteristics of having a point of view, has vertical fields vthat look like pillars lined, and the dark side on the facade. Video mapping is a three-act structure consisting of an opening, story/climax content, and closing, with the connection between the facade and the content, the video mapping has its own visual storytelling with clarity, realism, dynamism, and continuity is built according to the façade, such as in the action flow direction which makes the placement of objects or characters adjusted to the division of the facades. Video mapping NRMO tells about life, accepting, not giving up, and taking breaks for introspection in facing problems. Video mapping NRMO can create narrative immersion, several aspects produce this immersion, including the presentation of a narrative thatcontains life stories that can be conveyed well that can make appreciators focus and enjoy watching video mapping and providing an emotional connection with the storyline